Warunki bytowe mieszkańców Gorzowa Wielkopolskiego w czasach stalinowskich (1948-1956) = Standard of living in Gorzów Wielkopolski in the stalinist period (1948-1956) - Domke, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper focuses on the standard of living in Gorzów Wielkopolski in the time of the socalled Polish Stalinism, i.e. 1948-1956. It was doubtless the hardest time for the Poles after the war, characterised by terror and growing prices, demanding sacrifices from the inhabitants. The paper deals with the housing market, food supplies, commerce, services, catering business, prices and earnings.
Keywords: Życie codzienne; Gorzów Wielkopolski; Polska - historia - od 1944 r.